Identification of Ecological Hotspots for the Seagrass Posidonia oceanica via Metapopulation Modeling - Mari, Lorenzo; Melià, Paco; Gatto, Marino; Casagrandi, Renato (Frontiers in Marine Science, 2021)
The seagrass Posidonia oceanica is a benthic foundation species endemic to the Mediterranean Sea. It is a key component of coastal seascapes across the Mediterranean large marine ecosystem, where it plays fundamental ecological, physical, and economic roles. Despite the importance of this iconic seagrass species, a quantitative assessment of the interplay between local dynamics and basin-wide dispersal patterns is still lacking. Here we propose a Mediterranean-scale metapopulation model for P. oceanica, accounting for both demographic processes (inter-annual survival, vegetative growth, fruit production, seed establishment) and the spatial connectivity provided by current-driven dispersal of seagrass fruits. Model simulations are used to identify hotspots of seagrass population abundance, realized connectivity, and long-distance dispersal. Our results indicate that P. oceanica multi-functional hotspots, defined as species-suitable areas that rank high in all of the considered functional roles, are unevenly distributed in the four main sub-basins of the Mediterranean Sea, and along both the European and the African coastline. Our analysis also allows us to outline a remarkable geographical gap in protection: in fact, while many of the hotspots located along European coasts occur close to protected sites, the great majority of the hotspots lying on African coasts lack any form of protection. The identification of hotspots of P. oceanica metapopulation dynamics can thus help select regions that may serve as priority candidates for focusing conservation efforts.